Mesomechanism of Effects of Water on Strain Rockburst Prevention. (5th May 2021) - Liu, Beibei; Zhao, Fujun; Wu, Qiuhong; Wang, Bin; Tan, Jianuo; Feng, Tao
Abstract : In deep mining engineering, rockburst is an instantaneous release of a large amount of strain energy stored in rock mass, in which occurrence is closely related to initial high stress state and excavation unloading effect. Water can permeate the pores and cracks of rocks and often have a significant effect on the failure mode under stress. The effect of water on rockburst prevention and control has been observed by many researchers in rock engineering. However, the mechanism of rockburst prevention by means of water is seldom researched. In this study, the forming process of strain rockburst is introduced, and the key point to the mechanism of water spraying or water injection to prevent strain rockburst is that the presence of water could cause a transformation of failure mode of rocks during the strain rockburst incubation stage, thereby destroying its formation. In order to explore the specific influence of water on the change of rock failure mode, a crack propagation model with a single inherent main crack and two wing cracks was established, and the most-easily cracking angle ξ was proposed to analyze the mechanism of the failure mode influenced by different water contents. According to the calculated results of ξ, it was found that when rock is completely dry, the wing crack wing extends towards the loading direction, and ξ is around 90° which mainly induces its splitting failure; conversely, as the water content increases, the wing crack deviates from the loading direction; ξ is around 100° which mainly causes its shear failure. The proposed model in this study can reveal the mechanism of the effects of water on strain rockburst prevention in the view of mesoscale.